The Tax Dispute Settlement According To Justice And Court System In Indonesia - Rustian Mushawirya (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2019)
This research is motivated by an inconsistency in the regulation of the existence of tax justice in the Indonesian justice system, where the tax court is an appeal court against a decision in the field of tax dispute. A taxpayer who objects to the amount of tax that must be paid, can file a claim to the Directorate General of Taxes as the decision maker of tax disputes in the first stage. Legal problems are born from inconsistencies that occur in the concept of legal authority on the basis of the position held by the tax court and the Directorate General of Taxes on the Indonesian state system. Tax Justice is within the scope of the judicial body, while the Directorate General of Taxes is within the scope of the Executive body. This difference gave birth to a tendency towards partiality of the Directorate General of Taxes in deciding tax disputes because the disputed object was a decision of the government itself.This study uses legal materials as a research instrument, by carrying out several approaches namely the conceptual, the legal, and the case approach. This study aims to find the suitable theoretical and juridical foundation to create a tax justice system that is independent and give the legal certainty and protection to thethe interests of the people. The results of the study show that the tax court which is within the scope of the state administrative court must have the authority to try since the first stage and the stage of the appeal, which will end in the Supreme Court. This is done to avoid conflicts of interest within the executive body itself which results in the absence of legal protection for the people.KEYWORDS: tax justice, court, dispute, legal protection